High abilities or giftedness in Leadership: a proposal of identification and service (Research, Society and Development, 2022)
Leadership is one of de field of High Abilities or Giftedness (AHSD). Thus, this article aims to present the identification and a proposal of intervention to the students with Leadership characteristics in the Elementary School of a public network. The research was descriptive and action-research. One hundred and ninety students and fifteen teachers were participants. AHSD nomination questionnaires and checklist were applied. The results presented the indication of seven students, four boys and three  girls. Also, the enrichments I and II were realized to the indicated students in the resource room, in counter shift. The students were able to experience different activities in addition the school routine, which were positively evaluated by them and by the teacher-researcher responsible for the enrichments. It is understood that the study developed contributes to the discussions of AHSD in Leadership, especially to the young children.